Synthesis of cobalt oxide catalyst for PMS activation on organic dye removal - Tiu, Jia Jun (Nanyang Technological University, 2024)
This study was conducted to evaluate the catalyst efficiency to activate peroxymonosulfate for the removal of dyes, mainly Methyl Violet, Toluidine Blue O, and Acid Orange 7. Dyes, particularly those used in the textile industry, are considered organic pollutants. The discharge of wastewater from the textile industry may cause severe environmental impacts. The subject of catalyst is a topic of interest, due to its unique morphology that can affect the rate of catalysis. Cobalt oxide catalyst is a commonly used, low-cost transition metal oxide that was widely used in the air purification field. Therefore, this research investigates the efficiency of different types of Cobalt Oxide as a catalyst to activate PMS for the removal of dyes. By employing a comprehensive analytical approach, this study evaluates cobalt oxide synthesised via hydrothermal and simple chemical precipitation. The findings revealed that the catalytic activity is greatly influenced by its surface area, morphology, and elemental composition, with higher surface area and specific morphologies of nanorods and nanosheets demonstrating better dye degradation performance.